Educational Reform - Etiology, Types, Rules. - Andrzej Michał de Tchorzewski (Ignatianum University Press, 2018)
The subject of the article is the phenomenon of educational reforms. This phenomenon is one of the basic elements of pedagogical processes. In each historical period, all the educational reforms have their etiology and are characterized by specific consequences or the partial or total lack of them. The aim of the research on the above issue is to establish the general reasons for their conducting, to describe and explain the factors determining their process, making a typology of educational reforms and the rules for their implementation. All of these elements can significantly determine their quality. It is known, that this affects the effectiveness of school teaching and educational process. The school as an educational institution fulfills a social function having in mind the increase of the level of consciousness and pedagogical culture of each local environment, regional and national community and state. The basic methods that have been applied in the research were: the historical-comparative method and progressive method. The first enabled to implement the synthetic generalizations depicting mainly the etiology of educational reforms. The second method, in turn, was used to propose a typology of educational reforms and the formulation of the rules for their implementation. The research of these issues and the findings of them can be used for in-depth reflection and discussion on the searching for the conditions that optimize the processes of educational reforms and their effects.